The cavernicolous freshwater prawn in China, with description of two new species (Decapoda, Palaemonidae, Macrobrachium) - Jiang, Xuankong; Zhou, Jiajun; Ma, Kayan; Wang, Yaqin; Xie, Zhicai; Chen, Huiming (Zoosystematics and Evolution, 2025)
The karst area in southern China is recognized as a biodiversity hotspot for cave-dwelling organisms. However, the research of the cavernicolous species of the prawn genus Macrobrachium remains limited. This study aims to explore the species boundaries and diversity of this group and infer its phylogeny using an integrative approach. Molecular species delimitation analyses revealed five species excluding M. elegantum , for which molecular data were unavailable. Genetic gaps were observed among these species, with high interspecific distances (8.90%–27.43% for COI and 1.91%–9.63% for 16S) and low intraspecific distances (maximum 3.98% for COI and 0.47% for 16S). In contrast, morphological taxonomy identified three species and one species complex, which comprises three cryptic species. As a result, a total of six species were identified, including two new species, i.e. Macrobrachium guizhouense sp. nov. and M. parvum sp. nov. Among them, M. tenuipes and M. parvum sp. nov. are likely to be stygophiles, while the remaining species are likely to be stygobites. The phylogenetic trees based on (COI + 16S) revealed that these cave-dwelling species are polyphyletic, indicating the multiple independent cave invasions in the evolutionary history of this genus. Finally, these cavernicolous species exhibit opposite sexual dimorphism compared to epigean congeners, with females being larger than males. This may imply that they adopt a “pure search” mating mode. The findings enhance our understanding of the biodiversity and evolutionary history of subterranean Macrobrachium and provide fundamental data for the conservation of subterranean biodiversity.